ЕКОНОМІЧНИЙ МЕХАНІЗМ РЕАЛІЗАЦІЇ СТРАТЕГІЇ СІЛЬСЬКОГО РОЗВИТКУ ЗА УМОВ СТАЛОСТІ: МЕТОДИ ТА ІНСТРУМЕНТИ (ІННОВАЦІЙНА ЕКОНОМІКА, 2020)
Тимошенко М.М. ЕКОНОМІЧНИЙ МЕХАНІЗМ РЕАЛІЗАЦІЇ СТРАТЕГІЇ СІЛЬСЬКОГО РОЗВИТКУ ЗА УМОВ СТАЛОСТІ: МЕТОДИ ТА ІНСТРУМЕНТИМета. Поглиблення науково-методичних положень й обґрунтування практичних рекомендацій щодо розробки організаційно-економічного механізму реалізації стратегії сталого розвитку сільських територій України.Методика дослідження. Теоретико-методологічною основою дослідження є діалектичний, системний та синергетичний науковий підходи. У процесі дослідження використані такі спеціальні наукові методи: абстрактно-логічний, зокрема прийоми індукції та дедукції, аналогії та співставлення, операціоналізації понять; метод теоретичного узагальнення та аналізу й синтезу; різноманітні прийоми економіко-статистичного методу (статистичне спостереження, порівняння, табличний, графічний).Результати дослідження. Обґрунтовано теоретико-методичні засади формування економічного механізму реалізації стратегії сталого сільського розвитку України. Визначено, що єдиним шляхом імплементації стратегії стабільності розвитку сільських територій є налагодження економічного механізму, який включає методи та інструменти, які забезпечать певний тип рівноваги між соціальними, економічними та природоохоронними складовими життя сільського населення. Встановлено, що в основі сталого сільського розвитку повинні лежати дієві засоби, важелі та дії як економічного так і організаційно-управлінського характеру, які впливатимуть на інтереси господарюючих структур на селі (агроформувань різних форм власності та типів господарювання, фермерських господарств та сільських домогосподарств) і сприятимуть не лише активізації економічного життя на селі, а й досягнення соціального благополуччя й вирішення ряду екологічних проблем.Наукова новизна результатів дослідження. Доведено, що економічний механізм імплементації стратегії сталого розвитку сільських територій України, на відміну від існуючих підходів, доцільно розглядати як багатофункціональну систему політико-правових, нормативно-методичних, соціально-економічних, організаційно-виробничих, природоохоронних, інноваційно-інвестиційних та інших заходів, спрямованих на забезпечення реальних прогресивних змін у виробничій, соціальній та екологічній сферах сільської місцевості для підвищення добробуту і якості життя сільського населення та держави в цілому.Практична цінність результатів дослідження. Отримані результати, сформульовані висновки та пропозиції сприятимуть розв’язанню теоретичних та практичних проблем формування дієвого економічного механізму реалізації стратегії сталого соціально-економічного розвитку сільських територій як ключового елементу сучасної моделі сільської економіки України.Ключові слова: сільські території; економічний механізм; сталий сільський розвиток; соціально-економічні проблеми; стратегія; методи; важелі; інструменти. Тимошенко М.М. ЭКОНОМИЧЕСКИЙ МЕХАНИЗМ РЕАЛИЗАЦИИ СТРАТЕГИИ СЕЛЬСКОГО РАЗВИТИЯ В УСЛОВИЯХ УСТОЙЧИВОСТИ: МЕТОДЫ И ИНСТРУМЕНТЫЦель. Углубление научно-методических положений и обоснование практических рекомендаций по разработке организационно-экономического механизма реализации стратегии устойчивого развития сельских территорий Украины. Методика исследования. Теоретико-методологической основой исследования является диалектический, системный и синергетический научный подходы. В процессе исследования использованы такие специальные научные методы: абстрактно-логический, в частности приемы индукции и дедукции, аналогии и сопоставления, операционализации понятий; методы теоретического обобщения, анализа и синтеза; разнообразные приемы экономико-статистического метода (статистическое наблюдение, сравнение, табличный, графический).Результаты исследования. Обоснованы теоретико-методические основы формирования экономического механизма реализации стратегии устойчивого сельского развития Украины. Определено, что единственным путем имплементации стратегии стабильности развития сельских территорий является налаживание экономического механизма, который включает методы и инструменты, которые обеспечат определенный тип равновесия между социальными, экономическими и природоохранными составляющими жизни сельского населения. Установлено, что в основе устойчивого сельского развития должны лежать действенные средства, рычаги и действия как экономического так и организационно-управленческого характера, которые будут влиять на интересы хозяйствующих структур на селе (агроформирований различных форм собственности и типов хозяйствования, фермерских хозяйств и сельских домохозяйств) и способствовать не только активизации экономической жизни на селе, но и достижения социального благополучия и решения ряда экологических проблем.Научная новизна результатов исследования. Доказано, что экономический механизм имплементации стратегии устойчивого развития сельских территорий Украины, в отличие от существующих подходов, целесообразно рассматривать как многофункциональную систему политико-правовых, нормативно-методических, социально-экономических, организационно-производственных, природоохранных, инновационно-инвестиционных и других мероприятий, направленных на обеспечение реальных прогрессивных изменений в производственной, социальной и экологической сферах сельской местности для повышения благосостояния и качества жизни сельского населения и державы в целом.Практическая ценность результатов исследования. Полученные результаты, сформулированы выводы и предложения будут способствовать решению теоретических и практических проблем формирования действенного экономического механизма реализации стратегии устойчивого социально-экономического развития сельских территорий как ключевого элемента современной модели сельской экономики Украины.Ключевые слова: сельские территории; экономический механизм; устойчивое сельское развитие; социально-экономические проблемы; стратегия; методы; рычаги; инструменты. Tymoschenko M.M. ECONOMIC MECHANISM FOR THE IMPLEMENTATION OF THE STRATEGY OF SUSTAINABLE RURAL DEVELOPMENT UNDER THE CONDITIONS OF STABILITY: METHODS AND INSTRUMENTSPurpose. The paper deals with the deepening of scientific and methodological provisions and substantiation of practical recommendations for the development of organizational and economic mechanism for implementation of the strategy of sustainable development of rural areas of Ukraine.Methodology of research. The theoretical and methodological basis of the research is the dialectic, systemic and synergetic scientific approaches. In the process of research, the following special scientific methods have been used: abstract cand logical, in particular methods of induction and deduction, analogy and comparison, operationalization of concepts; method of theoretical generalization and analysis and synthesis; various methods of economic and statistical methods (statistical observation, comparison, tabular, graphic).Findings. It should be emphasized that theoretical and methodical principles of forming an economic mechanism for realization of the strategy of sustainable rural development of Ukraine are discussed. It is determined that the only way of implementing the strategy of the stability of rural development is to establish an economic mechanism that includes methods and tools that will provide a certain type of balance between the social, economic and environmental components of the rural population. It has been established that the basis of sustainable rural development should be the effective means, levers and actions of both economic and organizational and managerial character, which will affect the interests of the economic structures in the village (agricultural institutes of different forms of ownership and types of management, farms and rural households) and will promote not only the intensification of economic life in the countryside, but also the achievement of social well-being and the solution of a number of environmental problems.Originality. It is proved that the economic mechanism of implementation of the strategy of sustainable development of rural territories of Ukraine, in contrast to the existing approaches, should be considered as a multifunctional system of political, legal, methodological, socio-economic, organizational-industrial, environmental protection, innovation-investment and other measures. That are aimed to provide real progressive changes in the productive, social and environmental spheres of the countryside for improving the well-being and quality of life of the rural population and maintaining you are in general.Practical value. The obtained results, the formulated conclusions and proposals will contribute to solving theoretical and practical problems of forming an effective economic mechanism for implementing the strategy of sustainable socio-economic development of rural territories as a key element of the modern model of the rural economy of Ukraine.Key words: rural areas; economic mechanism; sustainable rural development; socio-economic problems; strategy; methods; levers; tools.